A holistic understanding of the effect of stress on adolescent well‐being: A conditional process analysis. (13th November 2019) - Branson, Victoria; Palmer, Edward; Dry, Matthew J.; Turnbull, Deborah
Abstract: Although traditional assumptions tend to conceptualize stress as inherently dysfunctional, psychological theory suggests that it is not intrinsically maladaptive. Contemporary models emphasize that the stress response can be differentiated into both negative and positive aspects, known as distress and eustress. Research examining the differential effect of positive and negative stress on adolescent well‐being is limited and has been hindered by a lack of appropriate measurement tools. The aim of the present study was to utilize the recently developed Adolescent Distress‐Eustress Scale to provide a balanced understanding of the impact of stress on positive mental health, holistically considering the effect of both distress and eustress on adolescent well‐being. One thousand eighty‐one Australian adolescents ( M age = 15.14, 54.03% female) completed an online survey composed of the Adolescent Distress‐Eustress Scale alongside measures of well‐being, self‐efficacy, psychological ill‐being, physical activity, and daytime sleepiness. Conditional process analysis suggested that distress exerted no direct influence on well‐being, with the observed negative relationship fully mediated by psychological and behavioural variables. Contrastingly, eustress was both directly related to increased well‐being and exerted an indirect effect through relationships with mediating variables. These results demonstrate that stress can have profoundly positive consequences. Theoretical contributions, implications for practice, and perspectives for future research are discussed.